2014
DOI: 10.1016/j.otsr.2013.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Does bone density of the greater tuberosity change in patients over 70?

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Sixteen studies (53%) were conducted prospectively; one study did not mention time of enrollment. Ten studies reported abnormalities in asymptomatic volunteers 1,11,16,18,21,23,24,33,39,47 ; 5 studies (4 of which were cadaver studies) reported prevalence in the general population 10,14,26,28,49 ; 8 included symptomatic patients 6,7,31,36,44,46,50,51 ; and 7 described patients with acute or chronic shoulder dislocations. 3,27,29,38,42,43,52 The majority of the studies used ultrasound to image the rotator cuff (43%; 13 of 30).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Sixteen studies (53%) were conducted prospectively; one study did not mention time of enrollment. Ten studies reported abnormalities in asymptomatic volunteers 1,11,16,18,21,23,24,33,39,47 ; 5 studies (4 of which were cadaver studies) reported prevalence in the general population 10,14,26,28,49 ; 8 included symptomatic patients 6,7,31,36,44,46,50,51 ; and 7 described patients with acute or chronic shoulder dislocations. 3,27,29,38,42,43,52 The majority of the studies used ultrasound to image the rotator cuff (43%; 13 of 30).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The current study is important because it presents biomechanical data unique to the greater trochanter, which is distinct from the greater tuberosity in terms of increased density, unique anatomic features, and role as part of a weightbearing joint. 13,33 Additionally, this study adds to the literature that a small amount of decortication (2 mm) is sufficient to significantly decrease the strength of repair. While Hyatt et al 27 performed an average of 5.6 mm of decortication, in this study we elected to decorticate just 2 mm of bone to recreate the amount of decortication that is typically performed clinically by surgeons.…”
Section: Discussionmentioning
confidence: 71%
“…Others propose careful tensioning of the screw at the end of the intervention to avoid a horizontal split in the bone block. Clavert et al [10] previously studied this phenomenon on the greater tuberosity of the humeral head and concluded that bone mineral density does not affect anchor purchase. Aziz et al [4] have also biomechanically confirmed the reduced screw purchase in osteoporotic humeri.…”
Section: Discussionmentioning
confidence: 99%